Kontribusi Perempuan Berwirausaha Untuk Meningkatkan Pendapatan Keluarga di Kecamatan Bukit Sundi Kab Solok - iwadiah, iwadiah; Susanti, Susanti (Jurnal Ilmiah Poli Bisnis, 2025)
The purpose of this study was to determine the contribution of women in working as entrepreneurs to family income in Bukit Sundi District, Solok Regency. The research method used is a descriptive analysis method. The type of data used in this study is quantitative data in the form of the amount of family income sourced from the income of women/wives, husbands' income and the income of other family members who work. Data were collected directly from respondents, namely 35 respondents who are entrepreneurs in the beef rendang industry and 30 respondents who are entrepreneurs in the cassava cracker industry, using interview techniques. The collected data were analyzed using the income formula and the share index formula (contribution) with the help of the Microsoft Excel program. The results of the analysis showed that the contribution of women in entrepreneurship to increase family income in Bukit Sundi District was 27.87% which came from the income of women working in the beef rendang industry with a contribution interval scale in the moderate criteria. While the contribution of women working in the cracker industry was 35.28% with a contribution interval scale in the sufficient criteria.